141 CASE REPORT: A PATIENT WITH CYSTIC FIBROSIS AND LUNG CANCER. (1st January 2005) - Wright, A.; Miller, S.; Hamilton, R.
Abstract : Introduction: Cystic fibrosis (CF) is a common, autosomal recessive disease characterized by chronic airway infections, exocrine pancreatic insufficiency, and intestinal dysfunction. Cancers described in patients with CF have generally been limited to the digestive tract, including small and large intestine and esophagogastric. We describe a case of lung cancer in a patient with CF. Methods: A 52-year-old white male was diagnosed with CF two years prior based on recurrent bouts of pancreatitis and an abnormal sweat test ([Cl] = 105 and 101 mEq/L [normal 0-40 mEq/L]). He had a 50 pack-year tobacco history that he quit prior to CABG, one year prior to diagnosis. A chest x-ray revealed a right lower lobe nodule. Fiberoptic bronchoscopy was performed, revealing no endobronchial lesions. A CT scan revealed the lesion along with enlarged mediastinal lymph nodes. Biopsies suggested poorly differentiated carcinoma. Final diagnosis was returned as small cell lung cancer (SCLC) with immunohistochemistry stains positive for broad-spectrum cytokeratin, synaptophysin, and neuron-specific enolase. A metastatic workup that included MRI brain; CT of the chest, abdomen, and pelvis; and a bone scan revealed no distant metastatic disease. He was begun on chemotherapy with etoposide (E) and cisplatin (P). Therapy was complicated by recurrent bouts of dehydration, pulmonary infection, and febrile neutropenia on one occasion. Repeat CT scans of the chest, abdomen, and pelvis revealed partial response of the original disease and a new lesion within the right middle lobe. Biopsy of this lesion revealed no malignancy. Chemotherapy was changed from EP to E + carboplatin (C). Repeat CT scans after two cycles of EC revealed worsening right middle and lower lobe disease, worrisome for lymphangitic spread. A CT-guided right lower lobe lesion biopsy returned as non-small cell lung cancer (NSCLC). Immunohistochemical staining was identical to the previous specimen and this was interpreted as large cell neuroendocrine carcinoma. Chemotherapy was changed to weekly docetaxel. Due to continued decline in pulmonary and performance status, therapy was discontinued shortly thereafter. The patient died approximately one month later. Conclusions: We report a man with a prior diagnosis of CF who developed SCLC and NSCLC. A MEDLINE search using the key words "cystic fibrosis" and "cancer" returned several articles and case reports of patients with CF and cancer, though the overwhelming majority were tumors of the digestive tract. In our search, we could only identify two other patients with nontransplanted CF and lung cancer.